2016
DOI: 10.1080/23328940.2016.1156801
|View full text |Cite
|
Sign up to set email alerts
|

Heat strain during military training activities: The dilemma of balancing force protection and operational capability

Abstract: Military activities in hot environments pose 2 competing demands: the requirement to perform realistic training to develop operational capability with the necessity to protect armed forces personnel against heat-related illness. To ascertain whether work duration limits for protection against heat-related illness restrict military activities, this study examined the heat strain and risks of heat-related illness when conducting a military activity above the prescribed work duration limits. Thirty-seven soldiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…34 Furthermore, during military training exercises, men may have comparatively tolerated working in the heat beyond the endurance limits. 22 This finding was re-echoed in a previous systematic review that men in the general population had a higher rate of all types of heat illnesses compared with women. 21 Although the incidence of heat stroke was lower in women compared with men in this review, the incidence of heat stroke among women has increased over the past 4 years.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…34 Furthermore, during military training exercises, men may have comparatively tolerated working in the heat beyond the endurance limits. 22 This finding was re-echoed in a previous systematic review that men in the general population had a higher rate of all types of heat illnesses compared with women. 21 Although the incidence of heat stroke was lower in women compared with men in this review, the incidence of heat stroke among women has increased over the past 4 years.…”
Section: Discussionmentioning
confidence: 84%
“…21 However, no previous review has investigated the epidemiology and risk factors of heat illness as well as gender responses to the heat tolerance test in men and women in the armed forces. Given that, heat illness can impact defence operational effectiveness and may result in acute loss of manpower and possible medical discharge from service, 22 the review should be conducted to inform policies.…”
Section: Open Accessmentioning
confidence: 99%
“… Such accounts have tended to focus not just on environmental conditions but also on exertion and exposure as areas of intervention. The Australian Defence Force for example articulates levels of exertion in relation to exposure through establishing recommended workload and work/rest cycles in relation to particular WBGT values . For other labor‐intensive industries, including those in the monsoon tropics, WHS policies follow a similar basic principle, typically recommending ‘work to rest ratios,’ ‘down tools policies,’ strategies to ‘self‐pace’ or otherwise reduce work intensity and strategies such as ‘rescheduling work so the hot tasks are performed during the cooler part of the day’ (see, e.g., Refs and ).…”
Section: Part 2: Implications For the Monsoon Tropicsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis reported that during, or at the end of work under heat stress, 35% of workers experience occupational heat strain, while 30% of workers report productivity losses (Flouris et al 2018a). However, occupational heat stress has been mainly studied to date in jobs associated with the military, construction, mining, agricultural, and metal industries (Brake and Bates 2002;Hunt et al 2016;Jay and Brotherhood 2016;Krishnamurthy et al 2017;Ryan and Euler 2017), as they include intense physical activity, wearing of protective clothing, and/or exposure to extreme ambient conditions. For outdoor workers it is well documented that high environmental heat strain has marked negative effects on workers' productivity (Ioannou et al 2017;Sahu et al 2013), whereas the effects on indoor workers are less clear and the impact more complex as industrial heat production and building architecture become factors of importance.…”
Section: Introductionmentioning
confidence: 99%